On the equation of electrical conductivity relaxation method to measure kinetic parameters of solid oxide fuel cell materials with a three-dimensional rectangular geometry. (23rd March 2021) - Yan, Fuyao; Yan, Mufu; Zhang, Yanxiang
Abstract: The electrical conductivity relaxation method has been widely used to measure kinetic properties of species transport process in solid oxide fuel cell materials using rectangular dense samples. It is found that the equation of ECR used in some studies is flawed. An improved equation is presented in this communication. Highlights: The 3D ECR equation used in some studies is flawed. The causality between the concentration and conductivity is analyzed. An improved ECR equation is presented.